Under bright lights : gay Manila and the global scene - Benedicto, Bobby, 1982- (Difference incorporated., 2014)
'Under Bright Lights' vividly describes the emergence in twenty-first century Manila of a 'bright lights' scene: a world composed of dance clubs, upmarket bars, party circuits, and other commercial sites that evoke images of a gay globe, but which remain bound to a landscape of disorder, mass poverty, and urban decay. Benedicto argues that queer world-making practices sustain élite desires for global modernity and the class, gender, and racial orders that structure urban life in the post-colony.